2012
DOI: 10.1007/s12010-012-9665-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enzyme Activity and Fiber Content of Soybean Cotyledon Fiber and Distiller’s Dried Grains with Solubles by Solid State Fermentation

Abstract: To increase the value of coproducts from corn ethanol fermentation and soybean aqueous processing, distiller's dried grains with solubles (DDGS) and soybean cotyledon fiber were used as the substrates for solid state fermentation (SSF) to improve feed digestibility. Aspergillus oryzae, Trichoderma reesei, and Phanerochaete chrysosporium were chosen as they produce desirable enzymes and are widely used in SSF for feed. The results showed that the cellulase and xylanase activities were significantly increased af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Soybean fiber with an original moisture content of 85% was adjusted to a moisture content of 75% by using soybean hulls, and the pH was adjusted to 5.0 as reported. 17 DDGS was hydrated to 85% of moisture and was adjusted to a moisture content of 75% with soybean hulls, using the same amount as for soybean fiber. Soybean hulls improve the porosity of substrates for better fungal growth as demonstrated in our previous study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean fiber with an original moisture content of 85% was adjusted to a moisture content of 75% by using soybean hulls, and the pH was adjusted to 5.0 as reported. 17 DDGS was hydrated to 85% of moisture and was adjusted to a moisture content of 75% with soybean hulls, using the same amount as for soybean fiber. Soybean hulls improve the porosity of substrates for better fungal growth as demonstrated in our previous study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…SSF of soybean cotyledon fiber and DDGS with the three individual fungi A. oryzae, T. reesei, and P. chrysosporium were previously investigated by Yang et al, 17 but the effect of coculturing using various combinations of the fungi was unknown. Thus, the objectives of this study were (1) to investigate if there is any synergistic effect among the three fungi based on the xylanase and cellulase production, (2) to determine the best combination of fungi for large-scale SSF, and (3) to examine the compositional change in soybean cotyledon fiber, DDGS, and soy-enhanced DDGS after largescale SSF.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on our previous study 2 of best fungus growth at moisture content of 75% or 70% as in Table 1, soybean fiber was adjusted to a moisture content of 75% using soybean hulls, which acted as inert materials to improve the porosity of the substrate and promoted better growth of fungi. 2 Previous results showed that 4% glucose might not be sufficient for P. irregulare to grow, therefore, different level of glucose was added to the substrate to investigate PUFA production. Table 3 shows the fatty acid composition of these treatments.…”
Section: Effect Of Incubation Time With Limited Glucose (4%) and Soybmentioning
confidence: 99%
“…SSF has been studied intensively for the production of enzymes, antibiotics, surfactants, and other value-added products. 2 Compared to the submerged fermentation in which nutrients are present in dissolved form in a large amount of water, SSF shows a great commercial potential due to its lower waste water production and operating expenses, simpler fermentation media requirement, superior productivity, and easier prevention of bacterial contamination. EAEP produces soybean cotyledon fiber and soy skim as co-products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation